Multivectorism politics in 2022 Qatar world cup: media relations analysis - Larisu, Zulfiah; Estrada, Philip R.; Ibnu, Syahrir; Nurmansyah, Mohammad; Darpin (Faculty of Communications Science, Dr. Soetomo University, 2023)
World Cup is a mega sports event enjoyed and built in the name of sport. However, as the community grows, World Cup becomes a sporting event and a political encounter. Each country is trying to be the best, and in order to achieve this, many seek mutual profit or increase power value during the event. Multivector Analysis was used to analyse social media content related to the Qatar 2022 World Cup. With the help of social media and Political Correctness, it becomes visible that these countries are trying to obtain their goals and match victory. Vulnerabilities, powers, and many faces accompany the condiments of the Qatar World Cup 2022. With a historical ancestry in FIFA, Political Correctness is like their anthems. Having a non-Western host would be a struggle against a larger country, resulting in a player exchange that allows them to become immigrants embroiled in heated political tensions because any country by nature still has a strong bias towards its land and its race.